Environment-friendly degradable plastic-wood material and preparation method thereof
By using PBAT resin as a matrix in the wood plastic material and adding flame retardant synergist and toughening modified components, the problems of flammable, poor flame retardant performance and insufficient toughness of the existing wood plastic material are solved, and the good biodegradability and high performance characteristics of the material are achieved.
Patent Information
- Application Number
- CN202411841946.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing plastic wood plastic materials are difficult to degrade, resulting in environmental pollution problems. At the same time, the materials are flammable, have poor flame retardant properties and insufficient toughness, making it difficult to meet high performance requirements.
PBAT resin is used as the matrix, and the flame retardant properties and toughening modification components are modified to modify the surface of the parallolite to improve the flame retardant performance and toughness of the material.
It achieves good biodegradability of plastic wood materials, improves flame retardant properties and toughness, extends the service life of the material, and broadens its application areas.
Smart Images

Figure CN119570213A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic-wood materials, and in particular to an environmentally friendly and degradable plastic-wood material and a preparation method thereof. Background Art
[0002] Wood plastic material is a composite material made of wood powder or other plant fibers and thermoplastic plastics through a specific processing technology. It has the dual characteristics of wood and plastic and is widely used in flooring, fences, outdoor benches, packaging materials, automotive interior parts and other fields. Among them, thermoplastic plastics usually choose polyolefin plastics, but polyolefin plastics are difficult to biodegrade and have an extremely long degradation cycle, which can reach about 200 years under normal conditions. Therefore, the development of degradable wood plastic materials can solve the environmental pollution problem caused by the difficulty of degrading polyolefin plastics, and has important social value and broad application prospects.
[0003] PBAT resin is a thermoplastic polymer material that can be completely decomposed by microorganisms in a natural state. It is in line with the contemporary concept of ecological green environmental protection. Using it as the matrix of plastic wood materials can give plastic wood materials good biodegradability. With the expansion of application fields, the performance requirements for plastic wood materials are getting higher and higher. The multifunctional development of plastic wood materials has become the focus of research by scientific researchers. Since wood powder and PBAT resin are flammable materials, they are easy to burn, and there is a molten droplet phenomenon during the combustion process, which can easily cause fires and bring huge losses to people. In addition, plastic wood materials need to have excellent toughness to avoid brittle fracture, deformation or creep when the material is subjected to external impact or stress, and ensure that the material can maintain its integrity when subjected to stress and extend its service life.
[0004] In the prior art, in order to improve the performance of plastic wood materials, functional additives are often used to fill and modify the material matrix. For example, the invention patent with the announcement number CN101570639B discloses a flame-retardant wood-plastic composite material and its preparation method. The invention material is made of modified waste plastics, wood fiber, intumescent flame retardant, lubricant and additives. By adding intumescent flame retardant to the matrix, the prepared wood-plastic composite material has good flame retardant properties. Therefore, high-performance plastic wood materials can be prepared by adding optimized components in the preparation process of plastic wood materials. Summary of the invention
[0005] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide an environmentally friendly and degradable plastic-wood material and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] An environmentally friendly and degradable plastic wood material comprises the following raw materials in parts by weight: 45-65 parts of PBAT resin, 30-40 parts of bamboo powder, 1-2 parts of coupling agent, 6-9 parts of flame retardant synergist, 5-8 parts of toughening modification component, 5-10 parts of filler, 1-3 parts of stabilizer, 2-4 parts of lubricant, and 0.5-1.5 parts of antioxidant.
[0008] Furthermore, the preparation method of the flame retardant synergist comprises the following steps:
[0009] D1: Add palygorskite and dimethyl sulfoxide solution into a reactor, perform ultrasonic treatment to form a uniform dispersion, then add pyridine-3,4-dicarboxylic anhydride and p-toluenesulfonic acid into the dispersion, after the addition, raise the temperature to 95-105° C., stir for 3-7 hours under the temperature condition, filter and separate the solid material, wash and dry to obtain modified palygorskite;
[0010] D2: The modified palygorskite is mixed with N, N-dimethylformamide, and ultrasonically dispersed for 15 to 25 minutes. Under continuous nitrogen conditions, pentaerythritol phosphate and a catalyst are added. The system temperature is raised to 90 to 110°C under stirring conditions, and the temperature is kept for 3 to 5 hours. The material is poured out, and after natural cooling, the solid material separated by filtration is the flame retardant synergist.
[0011] Furthermore, in step D1, the average particle size of the palygorskite is 4 μm.
[0012] Furthermore, in step D1, the mass ratio of palygorskite to pyridine-3,4-dicarboxylic anhydride is 1:0.1-0.3.
[0013] Furthermore, in step D2, the catalyst is any one of p-toluenesulfonic acid, aminosulfonic acid or trifluoromethanesulfonic acid.
[0014] It can be inferred that the principle of the above scheme is: in step D1, the surface of palygorskite contains hydroxyl groups, which can react with the anhydride groups in the pyridine-3,4-dicarboxylic anhydride structure under the action of p-toluenesulfonic acid to obtain modified palygorskite; in step D2, the carboxyl groups generated on the surface of the modified palygorskite due to the ring-opening reaction can react with the hydroxyl groups in the pentaerythritol phosphate structure under the action of a catalyst, thereby achieving surface modification of the palygorskite and obtaining a flame retardant synergist.
[0015] Furthermore, the preparation method of the toughening and modifying component comprises the following steps:
[0016] Under nitrogen protection, castor oil and methylphenyldichlorosilane are added to toluene, and the mixture is stirred evenly mechanically. Then, the accelerator is added. After the addition is completed, heating is started. After the system temperature reaches 65-75°C, constant temperature stirring is performed for 4-6 hours. The solvent is removed by rotary evaporation to obtain a toughening modified component.
[0017] Furthermore, the promoter is any one of triethylamine or pyridine.
[0018] It can be inferred that the principle of the above scheme is: since Si-C l in the structure of methylphenyldichlorosilane is highly active, under the action of the promoter, it can undergo continuous substitution reactions with the hydroxyl groups in the castor oil structure. By controlling the amount of the reactants, they can be continuously polymerized to form a polymer with a network structure, i.e., a toughening and modification component.
[0019] A method for preparing an environmentally friendly and degradable plastic-wood material comprises the following steps:
[0020] (1) Putting PBAT resin, bamboo powder and coupling agent into a high-speed mixer, mixing, then adding flame retardant synergist, toughening modification component, filler, stabilizer, lubricant and antioxidant, stirring and mixing at a stirring speed of 400 to 600 r / min for 1 to 2 hours to obtain a mixture;
[0021] (2) The mixed material is transferred to a twin-screw extruder for extrusion granulation, and finally the extruded granules are placed in a mold, and first hot-pressed and then cold-pressed to obtain the plastic wood material.
[0022] Furthermore, in step (1), the filler is any one of talcum powder, mica powder or titanium dioxide.
[0023] Furthermore, in step (2), in the twin-screw extruder, the head temperature of the extruder is set to 175-185°C, the temperature of zone 1 is set to 155-165°C, the temperature of zone 2 is set to 165-175°C, the temperature of zone 3 is set to 175-185°C, and the temperature of zone 4 is set to 180-190°C.
[0024] Beneficial effects of the present invention:
[0025] (1) The present invention uses PBAT resin as the matrix of the plastic wood material, which can make the prepared plastic wood material have good biodegradability, which is in line with the contemporary ecological green environmental protection development concept, and the prepared flame retardant synergist and toughening modification component are added to the matrix material, which effectively improves the flame retardant performance and toughness of the plastic wood material, prolongs the service life of the plastic wood material, and broadens its application field.
[0026] (2) The present invention uses a chemical connection method to graft nitrogen-phosphorus flame retardant on the surface of palygorskite to obtain a flame retardant synergist. Since the palygorskite is connected to each other by chemical bonds, the palygorskite can be evenly dispersed in the matrix, avoiding the negative impact caused by palygorskite agglomeration. On the one hand, palygorskite has a layered structure and can play a lamellar barrier role during the pyrolysis and combustion of the material, preventing the transfer of heat and oxygen and forming an effective physical barrier, thereby playing a flame retardant role. On the other hand, the nitrogen-phosphorus flame retardant grafted on the surface of the flame retardant synergist can further improve the flame retardant properties of the plastic wood material. The nitrogen element decomposes into ammonia, nitrogen, water vapor and other difficult-to-burn gases when heated, which helps to dilute the combustible gas and suppress the flame. The phosphorus element can decompose into phosphoric acid and polyphosphoric acid when burned to promote the formation of a carbon layer. Through the interaction between nitrogen and phosphorus elements, the flame retardant effect is enhanced, the occurrence of fire is avoided, the stability and reliability of the plastic wood material in various environments are ensured, and the application effect of the plastic wood material in various fields is effectively improved.
[0027] (3) The present invention prepares a toughening and modifying component as a filling and modifying agent for the plastic wood material, and utilizes the flexible silicon oxygen chain and castor oil molecules in the toughening and modifying component to effectively improve the toughness of the plastic wood material, thereby avoiding brittle fracture, deformation or creep of the material when subjected to external impact or stress, ensuring that the material can maintain its integrity when subjected to stress and extending its service life. In addition, the silicon element in the toughening and modifying component can produce a synergistic flame retardant effect with the flame retardant synergist, further improving the flame retardant properties of the plastic wood material.
[0028] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0030] Figure 1 This is an infrared spectrum test chart of the modified palygorskite and the flame retardant synergist prepared in Example 1 of the present invention.
[0031] Figure 2 This is an infrared spectrum test chart of the toughening and modifying component prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] 1. Preparation of flame retardant synergist
[0035] D1: 5 g of palygorskite with an average particle size of 4 μm and a dimethyl sulfoxide solution were added to a reactor, and ultrasonic treatment was performed to form a uniform dispersion. Then, 1.2 g of pyridine-3,4-dicarboxylic anhydride and 0.05 g of p-toluenesulfonic acid were added to the dispersion. After the addition was completed, the temperature was raised to 100° C., and after stirring at this temperature for 5 h, the solid material was separated by filtration, and the modified palygorskite was obtained after washing and drying.
[0036] D2: 5 g of modified palygorskite was mixed with N, N-dimethylformamide, and ultrasonically dispersed for 20 min. Under continuous nitrogen conditions, 1.4 g of pentaerythritol phosphate and 0.08 g of p-toluenesulfonic acid were added. The system temperature was raised to 105°C under stirring conditions and kept warm for 4 h. The material was poured out, cooled naturally, and the solid material separated by filtration was the flame retardant synergist.
[0037] The modified palygorskite and flame retardant synergist were analyzed by infrared spectroscopy using a Thermo Scientific Nicol et IS50 spectrometer. The test results are shown in Figure 1 ,Depend on Figure 1 It can be seen that in the infrared spectrum of modified palygorskite, 1760cm -1 The absorption peak of the ester group C=O appears at 1725 cm -1 The absorption peak of the carboxyl group C=O appears at 1630 cm -1 The absorption peak of C=N appears at 1405cm -1 The absorption peak of CN appears at 1750cm -1 The absorption peak of the ester group C=O appears at 1625cm -1 The absorption peak of C=N appears at 1408cm -1 The absorption peak of CN appears at 1281cm -1 The absorption peak of P=O appears at 1170cm -1 The absorption peak of POC appears at , and the absorption peak of the carboxyl group disappears.
[0038] 2. Preparation of toughening and modification components
[0039] Under nitrogen protection, add 4 g of castor oil and 2.6 g of methylphenyldichlorosilane to toluene, stir mechanically and evenly, then add 0.1 g of pyridine. After the addition, turn on the heating. After the system temperature reaches 70°C, stir at a constant temperature for 5 hours, and remove the solvent by rotary evaporation to obtain a toughening modified component.
[0040] The toughening and modification components were analyzed by infrared spectroscopy using a Thermo Scientific Nicol et IS50 spectrometer. The test results are shown in Figure 2 ,Depend on Figure 2 It can be seen that in the infrared spectrum of the toughened modified component, 1741cm -1 The absorption peak of the ester group C=O appears at 3010 cm -1 The absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears at 3050cm -1 The absorption peak of the carbon-hydrogen bond in the benzene ring appears at 1030cm -1 The absorption peak of Si-O bond appears at
[0041] 3. Preparation of wood plastic materials
[0042] (1) 45 g of PBAT resin, 30 g of bamboo powder and 1 g of titanate coupling agent PN-130 were added into a high-speed mixer and mixed well. Then, 6 g of flame retardant synergist, 5 g of toughening modification component, 5 g of talcum powder, 1 g of barium zinc composite stabilizer, 2 g of zinc stearate and 0.5 g of antioxidant 1076 were added. The mixture was stirred and mixed at a stirring speed of 400 r / min for 1 h to obtain a mixture.
[0043] (2) The mixed material is transferred to a twin-screw extruder for extrusion granulation, and the head temperature of the extruder is set to 175°C, the temperature of zone 1 is 155°C, the temperature of zone 2 is 165°C, the temperature of zone 3 is 175°C, and the temperature of zone 4 is 180°C. Finally, the extruded pellets are placed in a mold, and hot pressing and then cold pressing are performed to obtain the plastic wood material.
[0044] Example 2
[0045] Preparation of wood plastic materials
[0046] (1) 55 g of PBAT resin, 35 g of bamboo powder and 1.5 g of titanate coupling agent PN-130 were added into a high-speed mixer and mixed well, and then 8 g of flame retardant synergist, 7 g of toughening modification component, 8 g of talcum powder, 2 g of barium zinc composite stabilizer, 3 g of zinc stearate and 1 g of antioxidant 1076 were added, and stirred and mixed at a stirring speed of 500 r / min for 1.5 h to obtain a mixture;
[0047] (2) The mixed material is transferred to a twin-screw extruder for extrusion granulation, and the head temperature of the extruder is set to 180°C, the temperature of zone 1 is 160°C, the temperature of zone 2 is 170°C, the temperature of zone 3 is 180°C, and the temperature of zone 4 is 185°C. Finally, the extruded pellets are placed in a mold, and hot pressing and then cold pressing are performed to obtain the plastic wood material.
[0048] The preparation methods of the flame retardant synergist and the toughening and modifying component are the same as those in Example 1.
[0049] Example 3
[0050] Preparation of wood plastic materials
[0051] (1) 65 g of PBAT resin, 40 g of bamboo powder and 2 g of titanate coupling agent PN-130 were added into a high-speed mixer and mixed well. Then, 9 g of flame retardant synergist, 8 g of toughening modification component, 10 g of talcum powder, 3 g of barium zinc composite stabilizer, 4 g of zinc stearate and 1.5 g of antioxidant 1076 were added. The mixture was stirred and mixed at a stirring speed of 600 r / min for 2 h to obtain a mixture.
[0052] (2) The mixed material is transferred to a twin-screw extruder for extrusion granulation, and the head temperature of the extruder is set to 185°C, the temperature of zone 1 is 165°C, the temperature of zone 2 is 175°C, the temperature of zone 3 is 185°C, and the temperature of zone 4 is 190°C. Finally, the extruded pellets are placed in a mold, and hot pressing and then cold pressing are performed to obtain the plastic wood material.
[0053] The preparation methods of the flame retardant synergist and the toughening and modifying component are the same as those in Example 1.
[0054] Comparative Example 1
[0055] Preparation of wood plastic materials
[0056] (1) 55 g of PBAT resin, 35 g of bamboo powder and 1.5 g of titanate coupling agent PN-130 were added into a high-speed mixer and mixed well. Then, 8 g of flame retardant synergist, 8 g of talcum powder, 2 g of barium zinc composite stabilizer, 3 g of zinc stearate and 1 g of antioxidant 1076 were added. The mixture was stirred at a stirring speed of 500 r / min for 1.5 h to obtain a mixture.
[0057] (2) The mixed material is transferred to a twin-screw extruder for extrusion granulation, and the head temperature of the extruder is set to 180°C, the temperature of zone 1 is 160°C, the temperature of zone 2 is 170°C, the temperature of zone 3 is 180°C, and the temperature of zone 4 is 185°C. Finally, the extruded pellets are placed in a mold, and hot pressing and then cold pressing are performed to obtain the plastic wood material.
[0058] The preparation method of the flame retardant synergist is the same as that in Example 1.
[0059] Comparative Example 2
[0060] Preparation of wood plastic materials
[0061] (1) 55 g of PBAT resin, 35 g of bamboo powder and 1.5 g of titanate coupling agent PN-130 were added to a high-speed mixer and mixed evenly. Then, 7 g of toughening and modification component, 8 g of talcum powder, 2 g of barium zinc composite stabilizer, 3 g of zinc stearate and 1 g of antioxidant 1076 were added. The mixture was stirred and mixed at a stirring speed of 500 r / min for 1.5 h to obtain a mixture;
[0062] (2) The mixed material is transferred to a twin-screw extruder for extrusion granulation, and the head temperature of the extruder is set to 180°C, the temperature of zone 1 is 160°C, the temperature of zone 2 is 170°C, the temperature of zone 3 is 180°C, and the temperature of zone 4 is 185°C. Finally, the extruded pellets are placed in a mold, and hot pressing and then cold pressing are performed to obtain the plastic wood material.
[0063] The preparation method of the toughening and modifying component is the same as that in Example 1.
[0064] Comparative Example 3
[0065] Preparation of wood plastic materials
[0066] (1) 55 g of PBAT resin, 35 g of bamboo powder and 1.5 g of titanate coupling agent PN-130 were put into a high-speed mixer and mixed, and then 8 g of palygorskite with an average particle size of 4 μm, 7 g of toughening and modification component, 8 g of talcum powder, 2 g of barium zinc composite stabilizer, 3 g of zinc stearate and 1 g of antioxidant 1076 were added, and stirred and mixed at a stirring speed of 500 r / min for 1.5 h to obtain a mixture;
[0067] (2) The mixed material is transferred to a twin-screw extruder for extrusion granulation, and the head temperature of the extruder is set to 180°C, the temperature of zone 1 is 160°C, the temperature of zone 2 is 170°C, the temperature of zone 3 is 180°C, and the temperature of zone 4 is 185°C. Finally, the extruded pellets are placed in a mold, and hot pressing and then cold pressing are performed to obtain the plastic wood material.
[0068] The preparation method of the toughening and modifying component is the same as that in Example 1.
[0069] Comparative Example 4
[0070] Preparation of wood plastic materials
[0071] (1) 55 g of PBAT resin, 35 g of bamboo powder and 1.5 g of titanate coupling agent PN-130 were added to a high-speed mixer and mixed well. Then, 8 g of talcum powder, 2 g of barium zinc composite stabilizer, 3 g of zinc stearate and 1 g of antioxidant 1076 were added. The mixture was stirred at a stirring speed of 500 r / min for 1.5 h to obtain a mixture.
[0072] (2) The mixed material is transferred to a twin-screw extruder for extrusion granulation, and the head temperature of the extruder is set to 180°C, the temperature of zone 1 is 160°C, the temperature of zone 2 is 170°C, the temperature of zone 3 is 180°C, and the temperature of zone 4 is 185°C. Finally, the extruded pellets are placed in a mold, and hot pressing and then cold pressing are performed to obtain the plastic wood material.
[0073] Performance Testing
[0074] The plastic wood materials prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 are made into test specimens that meet the specifications, and the oxygen index of the test specimens is tested according to GB / T 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test"; the elongation at break of the test specimens is tested according to GB / T 1040.1-2018 "Determination of Tensile Properties of Plastics Part 1: General Principles". The specific test results are shown in Table 1:
[0075] Table 1 - Performance Test
[0076] Oxygen index (%) Elongation at break (%) Example 1 33.0 25.3 Example 2 33.6 26.1 Example 3 33.2 25.6 Comparative Example 1 31.4 17.5 Comparative Example 2 28.7 24.0 Comparative Example 3 29.8 23.9 Comparative Example 4 20.5 15.3
[0077] From the test results in Table 1, it can be seen that the samples prepared in Examples 1 to 3 have good flame retardant properties and toughness; no toughening and modifying component was added to the sample prepared in Comparative Example 1, and the toughness of the sample was poor compared with the example; no flame retardant synergist was added to the sample prepared in Comparative Example 2, and the flame retardant performance of the sample was not as good as that of the example; unmodified palygorskite was used to replace the flame retardant synergist in the sample prepared in Comparative Example 3, and it may be that the palygorskite was not organically modified, and agglomeration occurred in the matrix, resulting in a decrease in the flame retardant performance of the sample; no flame retardant synergist and toughening and modifying component were added to the sample prepared in Comparative Example 4, so the various properties of the sample were poor.
[0078] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. An environmentally friendly and degradable plastic wood material, characterized in that: The invention comprises the following raw materials in parts by weight: 45-65 parts of PBAT resin, 30-40 parts of bamboo powder, 1-2 parts of coupling agent, 6-9 parts of flame retardant synergist, 5-8 parts of toughening modification component, 5-10 parts of filler, 1-3 parts of stabilizer, 2-4 parts of lubricant and 0.5-1.5 parts of antioxidant.
2. The environmentally friendly and degradable plastic-wood material according to claim 1, characterized in that: The preparation method of the flame retardant synergist comprises the following steps: D1: Add palygorskite and dimethyl sulfoxide solution into a reactor, perform ultrasonic treatment to form a uniform dispersion, then add pyridine-3,4-dicarboxylic anhydride and p-toluenesulfonic acid into the dispersion, after the addition, raise the temperature to 95-105° C., stir for 3-7 hours under the temperature condition, filter and separate the solid material, wash and dry to obtain modified palygorskite; D2: The modified palygorskite is mixed with N, N-dimethylformamide, and ultrasonically dispersed for 15 to 25 minutes. Under continuous nitrogen conditions, pentaerythritol phosphate and a catalyst are added. The system temperature is raised to 90 to 110°C under stirring conditions, and the temperature is kept for 3 to 5 hours. The material is poured out, and after natural cooling, the solid material separated by filtration is the flame retardant synergist.
3. The environmentally friendly and degradable plastic-wood material according to claim 2, characterized in that: In step D1, the average particle size of the palygorskite is 4 μm.
4. The environmentally friendly and degradable plastic-wood material according to claim 2, characterized in that: In step D1, the mass ratio of palygorskite to pyridine-3,4-dicarboxylic anhydride is 1:0.1-0.
3.
5. The environmentally friendly and degradable plastic-wood material according to claim 2, characterized in that: In step D2, the catalyst is any one of p-toluenesulfonic acid, aminosulfonic acid or trifluoromethanesulfonic acid.
6. The environmentally friendly and degradable plastic-wood material according to claim 1, characterized in that: The preparation method of the toughening and modifying component comprises the following steps: Under nitrogen protection, castor oil and methylphenyldichlorosilane are added to toluene, and the mixture is stirred evenly mechanically. Then, the accelerator is added. After the addition is completed, heating is started. After the system temperature reaches 65-75°C, constant temperature stirring is performed for 4-6 hours. The solvent is removed by rotary evaporation to obtain a toughening modified component.
7. The environmentally friendly and degradable plastic wood material according to claim 6, characterized in that: The promoter is any one of triethylamine or pyridine.
8. A method for preparing the environmentally friendly and degradable plastic wood material as claimed in claim 1, characterized in that: The following steps are involved: (1) Putting PBAT resin, bamboo powder and coupling agent into a high-speed mixer, mixing, then adding flame retardant synergist, toughening modification component, filler, stabilizer, lubricant and antioxidant, stirring and mixing at a stirring speed of 400 to 600 r / min for 1 to 2 hours to obtain a mixture; (2) The mixed material is transferred to a twin-screw extruder for extrusion granulation, and finally the extruded granules are placed in a mold, and first hot-pressed and then cold-pressed to obtain the plastic wood material.
9. The method for preparing an environmentally friendly and degradable plastic-wood material according to claim 8, characterized in that: In step (1), the filler is any one of talcum powder, mica powder or titanium dioxide.
10. The method for preparing an environmentally friendly and degradable plastic-wood material according to claim 8, characterized in that: In step (2), in the twin-screw extruder, the head temperature of the extruder is set to 175-185°C, the temperature of zone 1 is set to 155-165°C, the temperature of zone 2 is set to 165-175°C, the temperature of zone 3 is set to 175-185°C, and the temperature of zone 4 is set to 180-190°C.
Citation Information
Patent Citations
Flame-retardant wood-plastic composite and preparation method thereof
CN101570639B
Fully degradable simulation material and preparation method thereof
CN109535670A
Bamboo powder / PBAT biodegradable material and preparation method thereof
CN113150509A
PBAT composite material and preparation method and application thereof
CN113388238A
Plant fiber-imitated degradable polyester composite material and preparation method thereof
CN114456557A